ROLE OF PSYCHOSOCIAL FACTORS IN COMPLETED SUICIDE A STUDY CONDUCTED AT RML MORTUARY FROM 2017 TO 2021 (Journal of Forensic Medicine & Toxicology, 2022)
Suicide is the second leading cause of death in 15-29 Years old population and close to 8 lakh people die due to suicide every year. India reported 381 suicides every day in 2019 with 3.4% rise in suicide rate as compared to 2018 .Total of 139,123 suicides occurred in India in 2019 which are alarming .Also amid of corona virus pandemic this year there is effect on psychological and social life of people and it may increase the suicide rates during and after pandemic. Our study conducted at RML mortuary from 2017-2021 where we collected 50 suicides and 50 non suicide cases and filled Performa and studied their Sociodemographic profile to find the difference in age, sex, socioeconomic status, Personality, previous attempt, physical and psychiatric history. In our study we found that lower education status i.e. illiterate , Male sex, maximum were between 20-40 years age group married , hanging as most common mode and no exact reason given was being most common cause which was stated by relatives of deceased.
Keywords: adolescents; Psychosocial functions; physical